THE INFLUENCE OF PRICE AND QUALITY OF SERVICE ON CUSTOMER SATISFACTION OF ONLINE TAXI TRANSPORTATION SERVICES (GRABCAR) - Dewi Nurmasari Pane (Quantitative Economics Journal, 2022)
The title of this research is "The Effect of Price and Service Quality on Customer Satisfaction of Online Taxi Transportation Services (Grabcar)". This study aims to test and find out more clearly how the influence of Price and Service Quality on Customer Satisfaction. This research uses quantitative methods involving 96 respondents. Data collection is done by using questionnaires. The data obtained were analyzed using statistical formulas, namely by using multiple regression analysis, the management of which was carried out with the SPSS Version 21. The quantitative analysis results showed that prices were partially positive and significant impact on Grabcar consumer satisfaction. The t-value of the price variable (X1) is 2.270 and the value of ttable is 1.66, then tcount> ttable (2.731> 1.66) and the value of Sig. <0.05 (0.026 <0.05). The magnitude of the effect of price (X1) on customer satisfaction (Y) of 0.195, which means that every time there is a price (X1), it will increase consumer satisfaction (Y) of 0.195 units. Service quality is partially positive and significant impact on Grabcar consumer satisfaction. The value of the tcount of the variable of human resource development (X2) is 7,967 and the value of the table is 1.66, then tcount> t table (7,967> 1.66) and the value of Sig. <0.05 (0,000 <0.05). The magnitude of the effect of service quality (X1) on customer satisfaction (Y) of 0.480, which means that every time there is an increase in service quality (X2), it will increase customer satisfaction (Y) by 0.480 units. Price and Service Quality are simultaneously significantly affected Grabcar consumer satisfaction. The calculated F value of 32.338 with a significant level of 0,000, greater than the F value of the table with a significant level of 95% (α = 0.05) is 59,071 = (59,071> 2.81).______________________________________________________________Keywords: Price, Service Quality and Customer Satisfaction